Representation of Verbal Sexual Violence in Academic Discourse: A Critical Discourse Analysis in Higher Education - Arsad (Lambaga Jurnal dan Publikasi Universitas Muhammadiyah Buton, 2025)
This study aims to analyze the representation of verbal sexual violence in academic discourse within higher education institutions using Norman Fairclough’s Critical Discourse Analysis (CDA) model. The research focuses on utterances containing elements of objectification, discursive strategies that normalize discrimination, and power relations within lecturer–student interactions. A qualitative approach with a case study design was employed. The research instrument consisted of a stimulus checklist containing 25 sentences representing potential forms of verbal sexual violence. This instrument was tested on 20 student respondents selected through purposive sampling. The validity of the instrument was established through a literature review and a readability test with initial respondents. Data were analyzed using Fairclough’s three-dimensional framework, namely text analysis, discourse practice, and social practice, and were triangulated with confirmatory interviews. The in-depth analysis reveals that although such utterances are often framed as humor, they reproduce patriarchal ideologies, reinforce asymmetrical power relations, and expose contradictions between the institution’s religious norms and everyday linguistic practices. This study makes a theoretical contribution by demonstrating that Fairclough’s CDA is effective in uncovering verbal sexual violence even in the form of subtle harassment or jokes, which have been largely overlooked in religious academic contexts. The novelty of this research lies in the identification of minor yet significant phenomena in religiously affiliated universities, showing that patriarchal power relations can still manifest through language even when the frequency of explicit cases is very low.